Mediterranean diasporas: politics and ideas in the long 19th century. Issue 3 (2nd September 2018) - Kurunmäki, Jussi; Heyberger, Bernard; Dialla, Ada; Zanou, Konstantina; Isabella, Maurizio
ABSTRACT: This round table discusses a collection that explores the circulation of ideas across and beyond the Mediterranean in the long nineteenth century, a space normally consigned to the margins of historiographical concerns and studied in discrete geographical areas. The commentators agree that the diasporic approach centred on biography taken by the collection demonstrates the existence of a plurality of liberal strands and political projects, highlights the importance of exchanges between European peripheries like Russia, the Adriatic and Greece, and challenges the notion of the derivative nature of eastern and oriental political culture. At the same time, the round table suggests new paths for future research, pointing to the desirability of producing a transnational conceptual history of liberalism that connects and compares East and West, and of applying the same transnational methodological approach to other seas.